Factores determinantes y su incidencia en la competitividad de las pequeñas microempresas del cantón Valencia. - Cabrera Macías, Vicky Andreina (2022)
The local and national economy is essential and has the possibilities for self-development, self- sufficiency, and growth, and the problem is that commercial micro businesses don't recognize factors that affect competitiveness to stay in the market. The objective of this research was to analyze the determining factors and their impact on competitiveness for the improvements in the economic conditions of small micro businesses in Valencia canton to get this purpose. This research used bibliographic and field research, among other theoretical methods: quantitative, empirical, analytical-synthetic methods: expert assessment, addition, descriptive and corrective research. The data of the local government of Valencia canton is based on 2,152 microenterprises, applying the calculation of sampling by strata, a sample of 145 owners obtained from polled using as an instrument the questionnaire that was validated. As a result of the relationship between the determinant factors (Competitors, Strategies, Competition, Weaknesses) and competitiveness (Strategic, Market, Customer, Take). There is a positive relationship. In a conclusion, the determining factors have an impact on competitiveness. Facing those results obtained the systematic random and Spearman methods used to improve the conditions of profitability in the market of small microenterprises.